Saving women's lives : strategies for improving breast cancer detection and diagnosis - Joy, Janet E. (Janet Elizabeth), 1953-; Penhoet, Edward E.; Petitti, Diana B. (National Academies Press, 2005)
Building on the 2001 report, Mammongrapy and Beyond, this book not only examines ways to improve implementation and use of new and current breast cancer detection technologies, but also evaluates the need to develop tools that identify women who would benefit most from early detection screening. It encourages more research that integrates the development, validation, and analysis of the types of technologies in clinical practice that promote improved risk identification techniques.